Generale e particolare nelle descrizioni e nelle spiegazioni linguistiche (Atti del Sodalizio Glottologico Milanese, 2019)
General and particular in linguistic descriptions and explanations. This paper presents a theoretical and methodological reflection on the relevance of particulars in linguistic descriptions and explanations and emphasizes the need to conjugate theoretical generalizations with close analysis of details in both descriptive and explanatory procedures. It also debates the different nature of the operations implied by describing and explaining linguistic phenomena in synchrony and diachrony and stresses the need to differentiate diachronic and historical explanations with respect to the level of historical particularism taken into account and the joint consideration of internal and external factors of language. The considerations presented are substantiated by the discussion of two descriptive problems, i.e. the Pro-drop parameter and the theoretical status of clitic pronouns, and two explanatory problems, i.e. the so-called “prepositional object” of Romance languages and the “inertial theory” of the development of chez in French.